1984
DOI: 10.1016/0014-5793(84)80452-4
|View full text |Cite
|
Sign up to set email alerts
|

The corrected nucleotide sequences of 5 S RNAs from six angiosperms

Abstract: The corrected nucleotide sequences of the cytoplasmic 5 S ribosomal RNAs of 6 angiosperms are reported. The previously reported sequences, reconstructed from oligonucleotide catalogs, had been suspected for some time to contain errors. The corrected seqeuences fit in a universal J-helii model for 5 S RNA secondary structure. The model involves the existence of a dynamic ~uilibrium between slightly different base-pairing schemes in two areas of the structure. Reconstruction of a phylogenetic tree from over 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…One can speculate that in the case of lupin seed one of these genes [ 181 represents a pseudogene as has assistance. The nucleotide sequence data for tobacco and maize 5 S rRNAs presented here ( fig.1) together with previous results [8,15] strongly support the hypothesis of the conservation of the 5 S rRNA nucleotide sequence of plants belonging to the same species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One can speculate that in the case of lupin seed one of these genes [ 181 represents a pseudogene as has assistance. The nucleotide sequence data for tobacco and maize 5 S rRNAs presented here ( fig.1) together with previous results [8,15] strongly support the hypothesis of the conservation of the 5 S rRNA nucleotide sequence of plants belonging to the same species.…”
Section: Discussionsupporting
confidence: 89%
“…The question was whether 5 S rRNA follows a phylogenic relationship in plants. So far, 213 5 S rRNA sequences have been established [8,15], 10 being of higher plant origin (table 1). In the case of the Gramineae and Papilionaceae, the sequences_ of two 5 S rRNAs are known in each case, whereas in the other species only one sequence had been resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenic Tree of 5S rRNA from Green Plants (Chlorophyta). We have determined the sequences of cytoplasmic 5S rRNAs from two green algae (7,14) and from six land plants [four Bryophyta species (15) and two Pteridophyta species (16) (7,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Fig. 2), we have constructed a phylogenic tree of green plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The duckweed 5S rDNA locus was among the first plant loci whose sequence was determined in the 1980s ( Vandenberghe et al, 1984 ). However, rDNA loci of duckweeds did not attract substantial attention until recently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these applications, the genetic diversity seen in duckweeds has stimulated a recent burst of studies examining duckweed genomics, molecular evolution, ecology, and biodiversity ( Appenroth et al, 2015 ; Laird and Barks, 2018 ; Ho et al, 2019 ). Despite the fact that the duckweed 5S rDNA was one of the first sequenced genes in plants ( Vandenberghe et al, 1984 ), the rDNA remains relatively poorly studied in duckweeds and in the Araceae. Our current knowledge of the molecular organization of the rDNA in the duckweed relates to the partial sequencing of 35S rDNA repeats from representative duckweed species in a study aiming to investigate the phylogenetic relationships and evolutionary history of Lemnaceae by Tippery et al (2015) and to whole genome sequences of Spirodela polyrhiza ( Michael et al, 2017 ) and Spirodela intermedia ( Hoang et al, 2020 ), which revealed important characteristics of the 35S and 5S rDNA loci.…”
Section: Introductionmentioning
confidence: 99%